1p−q
−1p+q
1pq
1pq(p−q)
Correct answer is B
1p - 1q ÷ pq - qp = q−ppq ÷ p2−q2pq
q−ppq x pqp2q2 = q−pp2−q2
−(p−q)(p+q)(p−q)
= −1p+q
Using △XYZ in the figure, find XYZ...
Find the equation of the locus of a point P(x,y) which is equidistant from Q(0,0) and R(2,1). ...
If a number is chosen at random from the set {x: 4 ≤x≤15}. Find the probability that it...
Find the values of y which satisfy the simultaneous equations x + y = 5, x2 - 2y2 = 1 ...
A sequence is given by 212,5,712,..... if the nth term is 25, find n...